2021
DOI: 10.3390/ma14185440
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass Applications: A Literature Review of Human Clinical Trials

Abstract: The use of bioactive glasses in dentistry, reconstructive surgery, and in the treatment of infections can be considered broadly beneficial based on the emerging literature about the potential bioactivity and biocompatibility of these materials, particularly with reference to Bioglass® 45S5, BonAlive® and 19-93B3 bioactive glasses. Several investigations have been performed (i) to obtain bioactive glasses in different forms, such as bulk materials, powders, composites, and porous scaffolds and (ii) to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 147 publications
(263 reference statements)
1
118
0
Order By: Relevance
“…In the in vitro study, BGs demonstrated an excellent ability to promote osteogenic differentiation, cell proliferation, and viability. Despite all these interesting features, it is also important to mention that BGs have some drawbacks, namely low fracture resistance in load bearing applications and the tendency to crystallize upon thermal treatments [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the in vitro study, BGs demonstrated an excellent ability to promote osteogenic differentiation, cell proliferation, and viability. Despite all these interesting features, it is also important to mention that BGs have some drawbacks, namely low fracture resistance in load bearing applications and the tendency to crystallize upon thermal treatments [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sol-gel route requires a specific chemical approach with precursor polymerization at room temperature to form the glass network [ 23 ]. Even if the melt-quenching route is the most employed, sol-gel offers some advantages, i.e., the synthesis temperature is relatively low, the composition ratio can be easily modified, the standardization of the product’s particle size can be organized to obtain pure samples with high uniformity, and constituents are allowed to be doped [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent advances in reconstructive dentistry are oriented towards using bioactive glasses due to the increased potential bioactivity and biocompatibility for bone regeneration procedures [ 85 ]. Recent studies reported that the biocompatibility of these biomaterials is correlated with the silicate-derived percentage range between 45 and 52%, which represents an optimal equilibrium between the tissue tolerance and the osteogenesis capability of the graft [ 85 , 86 , 87 , 88 , 89 ]. The bioglasses-acting mechanism is produced by the local release of ions and the generation of amorphous calcium phosphates precipitates that are able to generate a local change of the pH levels and osmotic flows [ 90 , 91 , 92 , 93 ].…”
Section: Bone Substitutes and Graftmentioning
confidence: 99%
“…Bioactive coatings improve not only bone formation but also adhesion and fixation and should be biocompatible, nontoxic, non-carcinogenic, or allergenic, and due to their flexibility to adjust their composition, they present an extraordinary versatility [14][15][16][17][18][19]. In this sense, they have been widely used for biomedical applications in tissue regeneration or as a part of matrixes for the release of smart and targeted drugs [20,21].…”
Section: Introductionmentioning
confidence: 99%